Rethinking PCTO with Student Voice: opportunities, challenges, and perspectives for combating school dropout - Pagani, Valentina; Rossi, Martina; Viscuso, Giuliana; Benvenuto, Guido; Pastori, Giulia (Form@re - Open Journal per la formazione in rete, 2025)
Career guidance and the enhancement of transversal skills are essential tools for preventing early school leaving and fostering active student engagement in their educational paths. In this context, the Pathways for Transversal Skills and Orientation (PCTO) represent a strategic opportunity. This paper presents the findings of an idiographic Student Voice study involving 297 students from five upper secondary schools. It highlights considerable variability in experiences, influenced by the level of student involvement in pathway design and the support provided by tutors. Furthermore, the paper explores the role of Student Voice in rethinking PCTO, emphasizing its potential to foster training-research initiatives with teachers and drive tangible changes in schools. Ripensare i PCTO con la Student Voice: opportunità, criticità e prospettive per il contrasto alla dispersione scolastica. L’orientamento e il rafforzamento delle competenze trasversali costituiscono strumenti fondamentali per prevenire la dispersione scolastica e favorire un coinvolgimento attivo degli studenti nel proprio percorso formativo. In questo quadro, i Percorsi per le Competenze Trasversali e l’Orientamento (PCTO) si configurano come un’opportunità strategica. Il presente contributo illustra i risultati di uno studio idiografico di Student Voice, che ha coinvolto 297 studenti di cinque scuole secondarie di secondo grado, evidenziando una marcata eterogeneità nelle esperienze, influenzata dal grado di partecipazione attiva nella progettazione del percorso e dal supporto ricevuto dai tutor. Il contributo analizza inoltre il ruolo della Student Voice nel ripensamento dei PCTO, sottolineandone il potenziale nel promuovere percorsi di Ricerca-Formazione con gli insegnanti e generare cambiamenti concreti nelle scuole.